The Effectiveness of Family-Based Digital Health Literacy in Improving Self-Health Monitoring in Active Farmers with Limited Mobile Phone Access - Supriadi Supriadi; Nur Aisyah; Indri Maydani; Sukmawati Sukmawati; Ulfarida Ulfarida (International Journal Of Health Science, 2026)
Active farmers are a group of workers at risk of experiencing various health problems due to physical workload, environmental exposure, and limited access to health information. Low digital health literacy and limited mobile phone ownership mean that self-health monitoring has not been carried out optimally. One effort to overcome this problem is through family-based digital health literacy. This study aims to analyze the effectiveness of family-based digital health literacy on improving self-health monitoring in active farmers who have limited access to mobile phones. This study used a Pre-Experimental Design with a One Group Pretest-Posttest Design approach. The study sample consisted of 32 active farmers selected using purposive sampling. Data were collected using a family-based digital health literacy questionnaire and analyzed univariately and bivariately using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The results showed that 17 respondents (53.1%) experienced an increase in digital health literacy scores after the intervention, while 15 respondents (46.9%) had scores that remained the same. The results of the Wilcoxon Signed Rank Test showed a Z value of -4.123 with Asymp. Sig. (2-tailed) = 0.000 (p < 0.05), indicating a significant difference between pre- and post-intervention scores. It was concluded that family-based digital health literacy effectively improved digital health literacy as an effort to support self-health monitoring in active farmers with limited access to mobile phones. This intervention can be used as a family-based health promotion strategy in community nursing practice, especially in rural communities.